Absent Inferior Vena Cava with Recurrent Deep Venous Thrombosis - Hemn Muhammed Mustafa; Hadi Muhamad; Araz Abdulfaraj (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2015)
Introduction: A congenitally absent inferior vena cava (IVC) is a rare condition that is recognized to be associated with deep venous thrombosis (DVT), especially in young adults. It may be not apparent until later in life. Case presentation: a previously healthy 24 years old male presented with left leg swelling and pain during walking, two years ago. During this admission he was investigated and diagnosed as absent IVC. He developed same manifestation but this time of the right side one year later. Conclusion: patients with congenital IVC anomalies associated with DVT are significantly younger in comparison to patients with isolated DVT of the lower limbs.